Development process of a clinical guideline to manage type 2 diabetes in adults by Ayurvedic practitioners - Chattopadhyay, Kaushik; Kapoor, Nitin; Heinrich, Michael; Mitra, Achintya; Mittal, Madhukar; Lewis, Sarah Anne; Greenfield, Sheila Margaret; Mukherjee, Shyamalendu; Pischel, Ivo; Jeemon, Panniyammakal; Tandon, Nikhil; Kinra, Sanjay; et al. (Frontiers in Medicine, 2023)
In the Indian subcontinent, type 2 diabetes mellitus (T2DM) is a common disease for which people consult Ayurvedic (traditional medical system) practitioners and use Ayurvedic medicines. To date, a high-quality clinical guideline, based on the best available scientific evidence, to manage T2DM by Ayurvedic practitioners is not available. Therefore, the study aimed to systematically develop a clinical guideline for managing T2DM in adults by Ayurvedic practitioners. Initially, we conducted a comprehensive systematic review assessing the effectiveness and safety of Ayurvedic medicines for managing T2DM and the certainty of the findings using the GRADE approach. Subsequently, based on the GRADE approach, we developed the Evidence-to-Decision framework, focusing on glycaemic control and adverse events. Based on the Evidence-to-Decision framework, a Guideline Development Group, comprising international members, made recommendations on the effectiveness and safety of Ayurvedic medicines in T2DM. The recommendations formed the basis of a clinical guideline, with further generic content and recommendations being adapted from the T2DM Clinical Knowledge Summaries of the Clarity Informatics (UK). The Guideline Development Group gave feedback on the draft version, which was used to finalise the clinical guideline. The clinical guideline provides basic information on T2DM, how it should be diagnosed and managed through lifestyle changes like diet and physical activity and Ayurvedic medicines, how the acute and chronic complications of T2DM should be detected and managed, and advice on topics like driving, work, and fasting including during religious/socio-cultural festivals. We systematically developed a clinical guideline for managing T2DM in adults by Ayurvedic practitioners.